2017
DOI: 10.1002/joc.4961
|View full text |Cite
|
Sign up to set email alerts
|

Climate and topographic controls on snow cover dynamics in the Hindu Kush Himalaya

Abstract: Snow governs interaction between atmospheric and land surface processes in high mountains, and is also source of fresh water. It is thus important to both climate scientists and local communities. However, our understanding of snow cover dynamics in terms of space and time is limited across the Hindu Kush Himalaya (HKH) region, which is known to be a climatically sensitive region. We used MODIS snow cover area (SCA) data (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), APHRODITE temperature data (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 51 publications
4
48
0
Order By: Relevance
“…In the case of trend analysis only the watersheds located in the northern part of the study area have a significant de- creasing trend during accumulation and melt season, which is in agreement with results from different studies in Asia and North America (Tang et al, 2013;Maskey et al, 2011;Gurung et al, 2017;Fassnacht and Hultstrand, 2015;Kunkel et al, 2016). During wintertime we could not see any significant trend, which is consistent with results from Dietz et al (2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the case of trend analysis only the watersheds located in the northern part of the study area have a significant de- creasing trend during accumulation and melt season, which is in agreement with results from different studies in Asia and North America (Tang et al, 2013;Maskey et al, 2011;Gurung et al, 2017;Fassnacht and Hultstrand, 2015;Kunkel et al, 2016). During wintertime we could not see any significant trend, which is consistent with results from Dietz et al (2012).…”
Section: Discussionsupporting
confidence: 91%
“…Azmat et al (2017) indicated that the watershed shows a consistent or slightly decreasing trend of snow cover, particularly over the high-altitude parts of the watershed during [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009], and in the 14-year analysis (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013), a slight expansion in the snow-covered area was observed in the whole basin. Gurung et al (2017), based on the analysis SCA data between 2003 and 2012, also obtained a decline in SCA, with a statistically significant negative correlation between SCA and temperature, which indicates that this trend is partly a result of increasing temperatures.…”
mentioning
confidence: 80%
“…We found evidence of a recent bottleneck, which is possibly a result of significant recent changes in habitat structure and rising winter temperature. The distribution and depth of snow in mountain regions are often influenced by wind and topography (e.g., aspect, slope), and microclimate, causing significant variation in snow cover, even across small geographical distances (Deems, Birkeland, & Hansen, ; Gurung et al, ). Royle's pika does not hibernate during winter and snow cover acts as a thermal insulator against extreme cold and fluctuating temperatures (Bhattacharyya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to analyse faecal pellets using metabarcoding to identify the plants in the diet of the Royle's pika and examine the effects of talus characteristics, topography and plant richness; abundance; and seasonal dynamics (pre‐ and postmonsoon) on diet, across five sites in the western Himalaya, India. Food availability (plant species’ presence and abundance; Huntly, Smith, & Ivins, ; Dearing, , ; Wilkening et al., ; Bhattacharyya et al., , 2014a; Bhattacharyya & Ray, ), habitat topography (elevation, slope, aspect; Walker, Halfpenny, Walker, & Wessman, ; Deems, Birkeland, & Hansen, ; Wilkening et al., ; Rodhouse et al., ; Gurung et al., ) and predation risk (rock cover, crevice depth, distance to the nearest area of talus; Calkins, Beever, Boykin, Frey, & Andersen, ; Bhattacharyya et al., ,b; Castillo, Epps, Davis, & Cushman, ; Bhattacharyya et al., ) significantly impact the foraging ecology of the Royle's pika and potentially influence access to nutritive plants, and thereby affect individual fitness (Bhattacharyya, ). For talus‐dwelling Ochotona spp., talus size (area) and connectivity between talus are known to influence the habitat occupancy (Franken & Hik, ).…”
Section: Introductionmentioning
confidence: 99%